The Perceptions of Five Years Old Group Students’ about Scientists - Et, Sümeyra Zeynep; Memiş, Esra Kabataş (Redfame Publishing, 2017)
The purpose of this research is to reveal the perceptions of students of five years old group about scientists. The practice was implemented with 76 students having education in five-age group continuing to various nursery schools located in the center of Kastamonu province. Before starting the practice, the teacher asked the questions of “Who is the scientist?” and made them thought with the aim of ensuring the awareness of students against scientist. Afterwards, the researchers asked the students to narrate their pictures while they collect the drawings. The paintings were coded by the researchers by using the descriptive analysis method. The codification was made individually at first and then together with all the researchers with the aim of ensuring the reliability of research. In the light of collected information, it was generally seen in the pictures of students that the work environment of scientists is constituted by the space and world and their gender is generally men and also, there was a small number of women scientist profile. It was also determined that the students emphasized the extraterrestrial life and drew the scientists as similar to astronauts and they used space crafts and planets in their paintings. In another finding, scientists were seen as the people who mostly conduct research and use potion in general. Another attractive research finding is that; a small number of students draw the scientist as person who use computer and study lesson. In the light of these findings, it can be told that the students were affected extremely from their environment (the movies and cartoon they watched, their families, etc.…).
Keywords: 4. Education; 10. No inequality